Acquisition and retention of knowledge and skills in basic life support among emergency medicine residents - Gloria, Fay Catherine K.; Erlyn A Sana, PhD (2011)
Survival of patients in cardiac arrest depends more on effective basic life support (BLS) rather than advanced treatment. Unfortunately, previous studies have shown that acquisition and retention of BLS knowledge and skills among healthcare professionals is poor. Among health professionals, Emergency Medicine (EM) physicians are expected to be most competent in performing BLS. In 2006, the American Heart Association (AHA) adopted the video-based, instructor-facilitated method of teaching BLS known as the ?practice-while-watching? (PWW) method to help ensure acquisition and retention of BLS knowledge and skills. This descriptive quantitative study analyzed the processes related to the acquisition and retention of BLS knowledge and skills among EM residents in a private tertiary medical center using a time series counterbalanced design. The EM residents underwent practical and written examinations prior to undergoing the AHA BLS for Healthcare Providers Course. They again underwent practical and written tests immediately, 1 week, 2 weeks, 1 month, and 4 months after the initial course. Their performances in the tests were compared and analyzed using paired t-test and analysis of variance. EM residents acquired knowledge and skills in BLS after being taught using the PWW method. The residents' motor skills deteriorated faster than knowledge did. During the study period, the EM residents were able to practice their BLS knowledge and skills by participating in the resuscitation of adult patients. No infant required CPR during the study period. The residents performed better in the Adult CPR skills tests than in the infant CPR skills tests. They also performed most poorly in the Infant One- and Two-Rescuer CPR skills test which had the most number of steps. Year level in residency and the use of BLS knowledge and skills during actual patient encounters did not appear to reinforce retention or cause decay of BLS skills and knowledge. The optimal mechanism for retaining knowledge and skill in BLS could not be determined in this study. Skills practice may have to be done as early as one week after the initial BLS course. EM residents should be given a chance to practice their BLS knowledge and skills under the guidance of a preceptor or instructor. It may also be worthwhile for EM residency training programs to organize their BLS training programs by institutionalizing review and retraining in BLS so that EM residents retain this essential lifesaving skill.
Thesis (Master of Health Professions Education)--University of the Philippines Manila
Panel Members: Erlyn A Sana PhD, Chair/Adviser; Melflor A. Atienza MD MHPEd, Reader/Critic; Nemuel S. Fajutagana MD MHPEd, Member; Maria Elizabeth M. Grageda PTRP MHPEd, Member; Reynante C. Mirano MD, Member.
Keywords: Life Support Care; Residents (Medicine) -- Philippines; Emergency medicine